A Critical Review of Multimodal Interventions for Cachexia. Issue 2 (24th September 2020) - McKeaveney, Clare; Maxwell, Peter; Noble, Helen; Reid, Joanne
ABSTRACT: Currently, there are no standardized treatments for cachexia or severe wasting. There is a growing consensus advocating multimodal interventions to address the complex pathogenesis and metabolic alterations in these conditions. This review examined multimodal treatments intended to alleviate and/or stabilize cachexia and severe wasting. The objectives of this review were to 1 ) identify multimodal interventions for the treatment of cachexia or associated wasting syndromes in patients with a chronic illness, 2 ) assess the quality of these studies, and 3 ) assess the effectiveness of multimodal interventions. Electronic databases including PubMed, MEDLINE, EMBASE, Scopus, Web of Science, Cochrane Library, CINAHL, PEDro, OpenGrey, and clinicaltrials.org were systematically searched using both text words and MeSH (medical subject heading) terms. The literature revealed a dearth of large, well-conducted trials in this area. Fourteen trials ( n  = 5 cancer, n  = 5 chronic obstructive pulmonary disease, n  = 4 chronic kidney disease) were included in this review. A total of 1026 patients were included across all studies; sample size ranged between 21 and 138 patients. Baseline and follow-up data were collected between 6 wk and 24 mo. All demonstrated some improvement in favor of the treatment groups, in relevant measures of body composition, nutrition, biomarkers, and functionality; however, caution should be applied due to the heterogenous nature of the interventions and small sample sizes. Overall, the evidence from this review supports the role of multimodal interventions in the treatment of severe wasting. However, randomized controlled trials with a powered sample size and sufficiently lengthy interaction period are necessary to assess if multimodal interventions are effective forms of therapy for improving body composition and nutritional and physical status in patients with cachexia and wasting. The protocol for this review is registered with Prospero (ID: CRD42019124374).